Degradability of nanocomposites after cyclic immersion in red and white wines - Saijai Tanthanuch; Boonlert Kukiattrakoon (Wolters Kluwer Medknow Publications, 2016)
Aims: To investigate surface microhardness of nanocomposites after cyclic immersion in red and white wines. Materials and Methods: Seventy-two specimens of each resin composite were prepared. Before immersion, baseline data of Vicker's microhardness were recorded and surface characteristics were examined using scanning electron microscopy (SEM). Three groups of discs (N = 23) were then alternately immersed in red wine, white wine, and deionized water (as a control) for 25 min and artificial saliva for 5 min over four cycles. The specimens were then stored in artificial saliva for 22 h. This process was repeated for 5 days following immersion in artificial saliva for 2 days. Subsequently, the process was repeated. After immersion, specimens were evaluated and data were analyzed by two-way repeated analysis of variance (ANOVA) and Tukey's honest significant difference (HSD) (α = 0.05). Results: Microhardness values significantly decreased after being immersed in the red and white wines (P < 0.05). SEM photomicrographs presented surface degradation of all groups after immersion in red and white wines. Conclusion: The effect of red and white wines on surface microhardness of nanocomposite restorative materials depended on the physical and chemical compositions of the materials and the types of wine.